Effect of resistance training on kinetic and kinematic indicators in jump athletes: a systematic review - Wenchao, R.; Soh, K. G.; Samsudin, S.; Zhao, Y.; Wang, X.; Zhang, X.; Cao, L. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background High, long, and triple jumps are athletic jumping events. Although they differ in technique and rules, they share many similar biomechanical characteristics. Resistance training is a key method for enhancing jumping performance and has gained attention. Different resistance training methods have been shown to significantly improve jumping performance. However, current research on these events remains insufficient, particularly in systematically analysing kinetic and kinematic indicators, exploring their relationships, and summarising common characteristics, which are crucial. These gaps hinder a deeper understanding of how resistance training affects jumping performance.